Citizen Science: Does It Make Sense for Nutrition Communication?. Issue 6 (November 2016) - Rowe, Sylvia; Alexander, Nick
Abstract : With the apparent success in recent years of citizen science (CS) projects in a variety of fields, the authors note the virtual absence of nutrition science in the current CS arena and explore the possibility of creating nutrition and other food-related CS projects. They argue that communicating such ventures might have beneficial effects on public understanding of nutrition/food science and on protecting the public from the misinformation too often promulgated in cyberspace. The article briefly summarizes the CS landscape and offers some modest suggestions for nutrition/food science projects that might lend themselves to a CS strategy. Finally, the authors discuss some of the communication challenges that might be encountered as nutrition science communicators enter this CS arena.